REDESIGN COMPANY REGULATIONS ALIGNED WITH LABOR LAW TO ENHANCE EMPLOYEE PERFORMANCE : A CASE STUDY OF PT.XYZ - Decinta Najlaputri; Emilia Fitriana Dewi; Aurik Gustomo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study analyzes the alignment of PT XYZ’s Company Regulations with Indonesian labor law and examines their implications for employee performance, using a qualitative socio legal design. Data were collected through semi structured interviews, document analysis, field observations, and legal inventory mapping of the company’s regulatory provisions against Law Number 6 of 2023, Government Regulation Number 35 of 2021, Government Regulation Number 36 of 2021, and relevant ministerial regulations. The findings show that PT XYZ’s existing Company Regulations partially comply with national labor standards but contain significant gaps, including outdated clauses on employment relations, overtime calculation, wage structure, grievance handling, and workplace protection. These inconsistencies have contributed to weak managerial accountability, limited employee participation, low motivation, and performance outcomes that fall below organizational targets. The study develops a revised Company Regulations design that integrates legal compliance with performance oriented governance through clearer procedures, transparent communication mechanisms, and structured performance indicators. The results demonstrate that legally aligned and managerially adaptive Company Regulations function not only as compliance instruments but also as strategic tools for strengthening employee performance, reducing turnover, and improving organizational sustainability.